Wheelchair lifter - Sumri, Muhamad Zamir; Anuar, Nurul Azwani; Hassan, Mohd Fahrul; Suhaini, Rozita; Ismail, Salmi; Syed Adnan, Syed Fadhil (Penerbit UTHM, 2017)
Basically, a wheelchair stair lift is a motorized, meaning by carrying a person seated in a wheelchair up and down stairs. A wheelchair lift, also known as a platform lift, or vertical platform lift is a fully powered device designed to raise a wheelchair and its occupant in order to overcome a step or similar vertical barrier (Figure 8.1). Wheelchair lifts can be installed in homes or businesses and are often added to both private and public vehicles in order to meet accessibility requirements laid out by the Americans with Disabilities Act of 1990 (ADA). These mobility devices are often installed in homes as an alternative to a stair lift, which only transport a passenger and not his/her wheelchair or mobility scooter. It is installed over the stairs in such a way that the stairs can still be used in the usual fashion. There is no need of breaking down or reconstructing the existing building.